O Bairro do Cerco do Porto: cenário de pertenças, de afectividades e de simbologias - Paula Guerra (2002)
At this point, we note that the Bairro is the scene and territory of a variety of social relationships, it is a place of shared experiences, taking as reference the collective identity of the Bairro. In this context, the practices of sociability are, in some way, the motive of the Bairro's history. The greater its magnitude depends on the existence of the Bairro as a social environment with its own life or simply a set of buildings and streets in an organized space. Several factors may contribute pivotally to the analysis of this Bairro as an highly relational context and of these factors is that we intend to report in this communication, evidencing logics and relationships that may or may not crystallize the experience of self and hetero social exclusion.